Mutational landscape and genetic signatures of cell‐free DNA in tumour‐induced osteomalacia. Issue 9 (11th April 2020) - Wu, Nan; Zhang, Zhen; Zhou, Xi; Zhao, Hengqiang; Ming, Yue; Wu, Xue; Zhang, Xian; Yang, Xin‐Zhuang; Zhou, Meng; Bao, Hua; Chen, Weisheng; Wu, Yong; et al.
Abstract: Tumour‐induced osteomalacia (TIO) is a very rare paraneoplastic syndrome with bone pain, fractures and muscle weakness, which is mostly caused by phosphaturic mesenchymal tumours (PMTs). Cell‐free DNA (cfDNA) has been regarded as a non‐invasive liquid biopsy for many malignant tumours. However, it has not been studied in benign tumours, which prompted us to adopt the targeted next‐generation sequencing approach to compare cfDNAs of 4 TIO patients, four patients with bone metastasis (BM) and 10 healthy controls. The mutational landscapes of cfDNA in TIO and BM groups were similar in the spectrum of allele frequencies and mutation types. Markedly, deleterious missense mutations in FGFR1 and loss‐of‐function mutations in MED12 were found in 3/4 TIO patients but none of BM patients. The gene ontology analysis strongly supported that these mutated genes found in TIOs would play a potential role in PMTs' process. The genetic signatures and corresponding change in expression of FGFR1 and FGF23 were further validated in PMT tissues from a test cohort of another three TIO patients. In summary, we reported the first study of the mutational landscape and genetic signatures of cfDNA in TIO/PMTs.